Shifted Jacobi spectral collocation method with convergence analysis for solving integro-differential equations and system of integro-differential equations - Doha, Eid H. H.; Abdelkawy, Mohamed A. A.; Amin, Ahmed Z.M. Z.M.; Baleanu, Dumitru (Nonlinear Analysis: Modelling and Control, 2019)
This article addresses the solution of multi-dimensional integro-differential equations (IDEs) by means of the spectral collocation method and taking the advantage of the properties of shifted Jacobi polynomials. The applicability and accuracy of the present technique have been examined by the given numerical examples in this paper. By means of these numerical examples, we ensure that the present technique is simple and very accurate. Furthermore, an error analysis is performed to verify the correctness and feasibility of the proposed method when solving IDE.